Allelopathic Potential of Centella asiatica Leaves on Seed Germination and Seedling Growth of Selected Field Crops - Kemboi, M. K.; Jeruto, P.; Mwamburi, L.; Korir, R. (Africa Environmental Review Journal, 2022)
Centella asiatica is a small, faintly aromatic, greenish-yellow leafy ubiquitous herbaceous plant of the Apiaceae family. It is a member of a weed community termed Hydrocotylo-Centelletum asiaticae association. Losses due to weeds have been estimated to be even more than those caused by insect pests and diseases. The objective of this study was to determine the allelopathic potential of Centella asiatica. Plant leaves were collected, shade dried followed by extraction using water and ethanol. The extracts were tested against maize, oats, rice, sorghum and wheat seeds. Ten (10) surface sterilized seeds were placed in each Petri dish. 25 millilitres of test extracts were used with double distilled water set as positive control and DMSO set as negative control. This was laid out in a Completely Randomized Design (CRD) with three replications at 25±2°C. The emerged plumule and radicle lengths were recorded after five (5) days and germination percentages calculated. The aqueous and ethanol extracts of Centella asiatica exhibited significant inhibitory effect on plumule and radicle lengths of maize, oats, rice, sorghum and wheat (p = 0.0000). On the number of seeds germinated, it showed increasing number of seeds germinated with reducing concentration of extracts. Oats and wheat did not germinate on ethanol extracts. Maize had the highest germination percentage of 97.5 while oats had the lowest of 24.17 in aqueous extracts. The ANOVA p-values of 0.0000 means that the leaf extracts of Centella asiatica had a statistically significant effect on plumule and radicle lengths of the test plants at P ≤ 0.05. It suggests that the extracts of C. asiatica interfered with the germination and growth of the test plants. This implies that there is a high likelihood for poor growth performance of these major staples in the presence of C. asiatica. The good allelopathic activity of C. asiatica can be utilised for making herbicides crucial for weed control. The results of study may be used to assess allelopathic potential against other field crops as well as further studies on the growth and development.